Tingkat Kemampuan Daya Tahan Jantung dan Pernafasan Mahasiswa Pendidikan Olahraga dan Kesehatan Universitas Pasir Pengaraian - Zulbahri Zulbahri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
This study aims to determine the level of endurance ability of the heart and breathing of students. This type of research is quantitative descriptive. The population of this research is 104 students of sport and health education at Pasir Pengaraian University, then selected by purposive sampling as a sample of 21 sons, semester II students of 2016. The data collection technique is by running a 1200 meter running test. Data were analyzed using the formula P = F / n X 100%. The results of this study indicate that, of the 21 samples known as many as 13 people (61.90%) are in the good category. Conclusion, the ability of heart endurance and breathing students of sports and health education is in the good category. Keywords: Ability of Heart Endurance, Respiration.